13,835 views

Let $X$ and $Y$ be two exponentially distributed and independent random variables with mean $α$ and $β$, respectively. If $Z$ = min $(X, Y)$, then the mean of $Z$ is given by

1. $\left(\dfrac{1}{\alpha + \beta}\right)$
2. $\min (\alpha, \beta)$
3. $\left(\dfrac{\alpha\beta}{\alpha + \beta}\right)$
4. $\alpha + \beta$

what is the role of min(x,y) here ?

Given n Random Var, the probability P(Yy)=P(min(X1…Xn)≤y) implies that at least one Xi be smaller than y. The probability that at least one Xi is smaller than y is equivalent to one minus the probability that all Xi are greater than y.

https://stats.stackexchange.com/questions/220/how-is-the-minimum-of-a-set-of-random-variables-distributed/10072#10072

edited by

it is just a property for min two independent exponential random variable
(not true for max independent exponential random variable)
http://llc.stat.purdue.edu/2014/41600/notes/prob3205.pdf

This might help:

derivation is not in syllabus

$X$ is an exponential random variable of parameter λ when its probability distribution function is

$$f(x) = \begin{cases}\lambda e^{-\lambda x} & x \geq 0 \\ 0 & x < 0 \end{cases}$$

For a > 0, we have the cumulative distribution function

$$F_x(a) = \int_0^a f(x) dx = \int_0^a \lambda e^{-\lambda x} dx = -e^{-\lambda x} \mid_0^a = 1 - e^ {-\lambda a}$$

So,

$$P\left\{X < a \right \} = 1 - e^ {-\lambda a}$$ and

$$P\left\{X > a \right \} = e^ {-\lambda a}$$

Now, we use $P \left \{X > a \right \}$ for our problem because our concerned variable $Z$ is min of $X$ and $Y$.

For exponential distribution with parameter $\lambda$, mean is given by $\frac{1}{\lambda}$.
We have,

$P \left \{X > a \right \} = e^ {-\frac{1}{\alpha} a}$

$P \left \{Y > a \right \} = e^ {-\frac{1}{\beta} a}$

So, \begin{align*}P\left \{Z > a \right \} &= P \left \{X > a \right \} P \left \{Y > a \right \} \left(\because \text{X and Y are independent events and } \\Z > \min \left(X, Y \right) \right)\\&=e^ {-\frac{1}{\alpha} a} e^ {-\frac{1}{\beta} a} \\&=e^{-\left(\frac{1}{\alpha} + \frac{1}{\beta} \right)a} \\&=e^{-\left(\frac{\alpha + \beta} {\alpha \beta} \right)a}\end{align*}

This shows that $Z$ is also exponentially distributed with parameter $\frac{\alpha + \beta} {\alpha \beta}$ and mean $\frac{\alpha \beta} {\alpha + \beta}$.

by

Such a simple a beautiful approach Arjun sir
Thanks for sharing the PDF ayush, I didnt know about the memoryless property.

I had some problem in understanding $Z>a$ iff $X>a$ and $Y>a$

So I tried to draw analogy using calculus: